Full-mouth rehabilitation in a patient with multiple caries: A case report - Putra, Anak Agung Istri Devi Wulandari; Yolanda, Yolanda (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Full-mouth rehabilitation of multiple caries can improve the quality of life. The selection of appropriate restorations on caries and teeth that have undergone post-endodontic treatment is critical to treatment success and enhances the quality of life. Purpose: This case report presents a full-mouth rehabilitation of a patient with multiple caries. Case: A 30-year-old man complained of multiple caries and pain in the posterior mandibular tooth, especially when eating and drinking (cold and hot), which interfered with his activities. The clinical examination found caries in teeth 16, 22, 24, 25, 26, 27, 36, 37, and 38 and a retained root of tooth 46. The percussion and biting tests were negative, while the sensibility test was positive. Case Management: Severe caries found in tooth 37 was managed with endodontic treatment and an indirect onlay restoration with lithium disilicate-based material. The retained tooth of 46 was extracted and restored with a partial denture. The other teeth, 16, 22, 24, 25, 26, 27, 36, 37, and 38, were treated by direct composite restoration. Holistic treatment was performed on all the problem teeth to support oral hygiene and was followed by dental health education. Conclusion: Full-mouth rehabilitation is essential for oral hygiene and can improve the quality of life. Education on maintaining oral hygiene is a must for protecting oral health.